ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN METODE ECONOMI ORDER QUANTITY (EOQ) PADA USAHA DYNASTY BAKERY DI AIRTIRIS (STIE Bangkinang Publishing, 2020)
This study aim to determine the analysis of raw material invetory control by Economic Order Quantity (EOQ) method in Dynasty Bakery Business in Airtiris. The data analysis method used is the EOQ method, the safety stock and the re-order point. Based on the resuts of the analysis, the optimum purchase quantity according to conventional company policy is 749,25 Kg with a purchase frequency of 40 time. Whereas based on the EOQ method the optimum purchase quantity is 1.579,47 Kg with a purchase frequency of 19 time. Total inventory cost with conventional company pollicy is Rp. 1.837.537 whearese based on the EOQ is Rp.1.423.103. So by using the EOQ method yhe company can streamline inventory costs by Rp. 414.434 meanwhile, for safety inventory and reorder points according to the company policy does not exist, while EOQ method there safety stock is 786,31 Kg and r-eorder point is 1.026,07 Kg.